(untitled) (Heritage, 2023)
Frequent use of psychoactive drugs, alcohol and tobacco can lead to pathological changes in the vocal cords. The aim of this study is to analyze the connection between the consumption of psychoactive substances and disturbances in the quality of the voice by reviewing the previous literature. Voice disorders in users of psychoactive substances occur over time, due to the appearance of organic changes in the vocal apparatus. Marijuana smoke causes irritation of the mucous membrane of the larynx, which causes hoarseness and hoarseness in the voice. The effect of electronic cigarettes on voice quality is milder compared to the effect of conventional cigarettes. The results of this study also show that drug users have lower results in the domain of social functioning compared to alcohol and tobacco users. The findings of this study suggest that users of psychoactive substances have respiratory disorders and worse lung function, changes in vocal folds, disturbance of auditory and perceptual parameters of voice quality and worse quality of life. Additional implications suggest the necessary help and support of speech therapists in educating users of psychoactive substances about the ways of their use and their connection with voice disorders and quality of life as a whole.